Optimal consumption and investment under relative performance citeria with Epstein-Zin utility - Jodi Dianetti; Frank Riedel; Lorenzo Stanza (Bielefeld University, Center for Mathematical Economics (IMW), 2024)
We consider the strategic interaction of traders in a continuous-time financial market with Epstein-Zin-type recursive intertemporal preferences and performance concerns. We derive explicitly an equilibrium for the finite player and the mean-field version of the game, based on a study of geometric backward stochastic differential equations of Bernoulli type that describe the best replies of traders. Our results show that Epstein-Zin preferences can lead to substantially different equilibrium behavior.
urn:nbn:de:0070-pub-29871065
Keywords: C02; C61; C61; C73; G11; 330; Mean field games; portfolio choice; recursive utility; stochastic differential utility; BSDEs